Optimal Combination of Features on Gadoxetate Disodium-enhanced MR Imaging for Non-invasive Differential Diagnosis of Hepatocellular Carcinoma: The JAMP-HCC Study - Ichikawa, Shintaro (Magn Reson Med Sci, 2020)
PURPOSE: To determine the optimal combination of gadoxetate disodium-enhanced magnetic resonance imaging (MRI) findings for the diagnosis of hepatocellular carcinoma (HCC) and to compare its diagnostic ability to that of dynamic computed tomography (CT) in patients with chronic liver disease. METHODS: This multi-institutional study consisted of two parts: Study 1, a retrospective study to determine the optimal combination of gadoxetate disodium-enhanced MRI findings (decision tree and logistic model) to distinguish HCC (n = 199) from benign (n = 81) or other malignant lesions (n = 95) (375 nodules in 269 patients) and Study 2, a prospective study to compare the diagnostic ability of gadoxetate disodium-enhanced MRI to distinguish HCC (n = 73) from benign (n = 15) or other malignant lesions (n = 12) with that of dynamic CT (100 nodules in 83 patients). Two radiologists independently evaluated the imaging findings (Study 1 and 2) and made a practical diagnosis (Study 2). RESULTS: In Study 1, rim or whole enhancement on arterial phase images, signal intensities on T(2)-weighted/diffusion-weighted/portal venous/transitional/hepatobiliary phase images, and signal drop on opposed-phase images were independently useful for differential diagnosis. In Study 2, the accuracy, sensitivity, negative predictive value, and negative likelihood ratio of the CT decision tree (reader 2) were higher than those of MRI Model 2 (P = 0.015–0.033). There were no other significant differences in diagnostic ability (P = 0.059–1.000) and radiologist-made practical diagnosis (P = 0.059–1.000) between gadoxetate disodium-enhanced MRI and CT. CONCLUSION: We identified the optimal combination of gadoxetate disodium-enhanced MRI findings for HCC diagnosis. However, its diagnostic ability was not superior to that of dynamic CT.